How effective is circuit training on physical fitness? A high-intensity study in the sport of futsal - John Paul C. Suniga; Joselito M. Custodio; Patrick John B. Roldan; Hatem A. Shlool; Mohammad Fayiz Abumoh'D (Tanjungpura Journal of Coaching Research)
Background and Study Aim. Physical fitness is a crucial component that supports optimal performance in sports, including futsal, which demands a combination of endurance, strength, agility and speed. This study aims to analyze the effectiveness of high-intensity circuit training on improving the physical fitness of futsal players.